Ubezpieczenia indywidualne na życie z funduszem kapitałowym na rynku polskim : analiza struktury produktu i rynku w Polsce w latach 2005-2005 - Rajczakowska, Joanna (Individual Life Insurances with Capital Investment in the Polish Market. The Analysis of Product and Market Structure Between 2000 and 2005, 2008)
Growth of services connected with providing life insurances is one of the main factors generating the rise of modern - in the way we understand that today - financial markets. A basic element that characterizes the sale of that product is the feature of massness of this market of products and financial services. Insurance products let the numerous groups of consumers to participate in financial systems, accumulate and concentrate individual capital in long periods of time, which at the same time strengthens the processes of capital market growth. This article has two main objectives. Its first aim is to discuss the specific features of insurance with capital fund, and the other aim is to characterize the market, analyzing the product sale as well as to indicate and discuss the influence of factors that boost its sale. To achieve this goal, in the article the insurace-investment product has been characterized and the structure of sale in the years 2000-2005 has been discussed. In the last section of the article, The New Forms of Insurance and the Needs of the Market, the factors whose influence brings about the rise of level of sale of this form of insurance have been indicated. Also, the advantages and disadvantages of this kind of insurance have been disscussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 395-404